TANTANGAN HARMONISASI REGULASI DIGITAL DI INDONESIA: PERBEDAAN KERANGKA HUKUM NASIONAL DAN INTERNASIONAL SERTA KETERBATASAN SUMBER DAYA DALAM AKSELERASI SINKRONISASI - Gunawan Widjaja (NETIZEN: JOURNAL OF SOCIETY AND BUSSINESS, 2025)
The rapid development of digital technology requires harmonisation of regulations between national and international legal frameworks so that Indonesia can keep pace with global dynamics while maintaining domestic regulatory sovereignty. This study examines the challenges of digital regulatory harmonisation in Indonesia, focusing on the differences in substance and legal mechanisms between national regulations and international standards, as well as the limitations of resources in terms of human resources, technological infrastructure, and institutions that hinder the acceleration of regulatory synchronisation. The research method used is a legal-normative literature review. The results reveal that legal framework disparities remain significant, particularly in personal data protection, fintech, and cybersecurity, compounded by limited resource capacity, which slows down regulatory harmonisation. This study recommends regulatory reform through increased human resource capacity, digital infrastructure development, and improved institutional coordination as key strategies for accelerating digital regulatory harmonisation in Indonesia. With these steps, Indonesia can increase its competitiveness and trust in the global digital ecosystem without sacrificing national legal sovereignty.